Cultivating Islam Nusantara in Indonesia’s Pesantrens: a Promising Deradicalisation Strategy? - Irfan L Sarhindi (Lakpesdam PCNU Kota Salatiga, 2020)
The purpose of this study is to demonstrate to what extent the cultivation of discourse of Islam Nusantara in Indonesia‘s pesantren. This is a qualitative research. The method of collecting data is through documentation. The research finding showed that Pesantrens had proven themselves to be the fortress of cultural Islam. They have maintained the moderate face of Indonesian Islam. Their flexibility has shown as useful when Islamic education is the concern. However, the use of media as the source of Islamic knowledge has a certain degree that